The Effect of Learning Interest andPowerpoint Learning Media on Students' Learning Achievement in Civics Subject in Senior High School South Sukoharjo - Amsyari, Farizal; Bambang Sumardjoko (Jurnal Teknologi Pendidikan, 2024)
The purpose of this study was to see how the involvement of learning interest and powerpoint learning media affects students' learning achievement. This study is a correlational study and was conducted in high schools in South Sukoharjo with a total of 3 schools. The sample in this study was 280 people. Information on learning achievement was obtained through a questionnaire. Data analysis used the t test and F test to determine the partial and simultaneous effects. The results showed a strong and good correlation between learning interest, powerpoint learning media and learning achievement. Learning interest and powerpoint learning media contributed 56% to learning achievement, while factors not included in this study contributed 44% to the variation. This study suggests examining additional variables that affect learning achievement in more detail.